Dune fields in Jericoacoara: human intervention as a possible indicator of changes in the morphological dynamics - Antonio Jeovah Meireles; Adryane Gorayeb; Narcélio de Sá Pereira Filho (Confins)
Coastal dunes play an important role in the sediment transport of the coastal zone. The morphology of the Jericoacoara National Park in the northeastern Brazilian state of Ceará consists of a headland covered by a mobile dune field consisting of large mobile barchans dune fields that migrate from east to west. These dunes are responsible for the bypass and transportation of essential sediments for the maintenance of the coastline without cumulative erosive effects. The present study focused on the morphodynamic evolution of these isolated mobile dunes through the recovery of multitemporal Landsat and QuickBird satellite images of the years between 1975 and 2010. The spatiotemporal analysis of the distribution and morphology of these dunes over this 35-year period revealed significant shifts in their area, perimeter, and movement patterns. It was possible to confirm that the flow of material and energy was linked to a process of continuous migration in the direction of the beach. The dynamics of the dune migration in the years following 2000 was established, indicates possible impacts on the morphology of the dunes resulting from the increase in tourism within the area. These changes were most significant between 2001 and 2005, possibly reflecting a anthropogenic impacts.